2022
DOI: 10.3390/f14010017
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Cones Production in a Silver Fir (Abies alba Mill.) Clonal Seed Orchard

Abstract: The current study is the first to describe fertility dynamics in a Silver fir (Abies alba Mill.) seed orchard and among the few reporting related information from a mature seed orchard. The research aim was to evaluate the female cone production in order to provide support to future management measures. Observations were conducted in a clonal seed orchard from the Eastern Carpathians over six years; all the ramets of 44 clones and the zero-inflated data were analyzed with generalized lineal mixed effects model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…As the result of a recent study indicating a higher influence of the year and probably of the sensitivity to climate, there was less variability between clones for cone production in a silver fir (Abies alba Mill.) seed orchard [24]. It was also reported that the repeatability of mean annual clone production suggested the moderate continuity of cone crops in the production rank of individual clones, while heritability was under genetic control [24].…”
Section: Cone Productionmentioning
confidence: 99%
“…As the result of a recent study indicating a higher influence of the year and probably of the sensitivity to climate, there was less variability between clones for cone production in a silver fir (Abies alba Mill.) seed orchard [24]. It was also reported that the repeatability of mean annual clone production suggested the moderate continuity of cone crops in the production rank of individual clones, while heritability was under genetic control [24].…”
Section: Cone Productionmentioning
confidence: 99%
“…Seed years occur at two-year intervals at lower altitudes, while at higher altitudes, they occur every 3-5 years [289,290]. The differences in fir fertility of cones in Romania reached up to 11.2 times when comparing good mass years to poor years [291]. The mean dispersal distances of seeds from trees ranged from 9.9 m in pure fir stands to 21.5 m in mixed forest in Spain [292].…”
Section: Seed Production and Nursery Management In The Context Of Cli...mentioning
confidence: 99%
“…Fir seeds should be collected at morphological (hard) maturity, which precedes physiological maturity, when the seeds can germinate [298]. Fir cones are usually collected manually by picking from standing or felled trees [303] or from seed orchards established for this purpose [291]. Using Czechia as an example, the expanding production of silver fir seed material points to rising demand for fir seed material in the context of an increased need for seedlings for the reforestation of large clearings following the 2017-2019 bark beetle calamity ( [67]; Table 3).…”
Section: Seed Production and Nursery Management In The Context Of Cli...mentioning
confidence: 99%
“…Pentru menţinerea nivelului de diversitate genetică şi în loturile de seminţe, amestecarea diferitelor fonduri de gene este un mijloc eficient, deşi acest aspect este condiţionat de o serie de mecanisme privind sincronizarea înfloririi, unde adaptarea regională ar putea avea un rol important. Studii realizate în ceea ce privește fructificația și rata de panmixie în plantaje de brad au indicat că totuși participarea clonelor este redusă (Teodosiu et al 2022).…”
Section: Discuțiiunclassified